Determination of Important Parameters in Affecting the Uptake of Reactive Black 5 by Chitosan Beads through Statistical Approach - Yi-Pin Phung; Siew-Teng Ong; Pei-Sin Keng (Journal of Chemistry)
Chitosan which can be obtained from fishery waste was studied as an alternative source to remove pollutants in the wastewater. The adsorption process of Reactive Black 5 (RB5) by chitosan was studied under batch experimental condition to identify the optimum condition in which the dye can be removed at a higher rate. The best fit kinetics model was determined to be the pseudo-second-order kinetics. From the isotherm study, the experimental result was better explained by Freundlich isotherm. Plackett-Burman was employed to identify the influential variables affecting the dye uptake. Response surface methodology (RSM) was used to determine the interactions between the factors and their optimum levels for maximum uptake of RB5. The optimum condition for the highest percentage uptake of RB5 dye was determined to be at pH 4, agitation rate of 200 rpm, sorbent dosage of 1.0 g, contact time of 300 minutes, and initial dye concentration of 25 mg/L.